PENGARUH PROMOTION MIX TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI ARTOTEL BUTIK HOTEL SURABAYA - yuliana yuliana; yessica Livia Chaterina Junnifer (Jurnal Hospitality dan Manajemen Jasa, 2016)
The Growth of the hospitality industry in Surabaya is characterized by an increase in tourist numbers and the increase of new hotels in Surabaya. Competition is increasing in the hospitality industry Surabaya. Therefore, to make occupancy rate stable, each hotel makes several attempts. One of them is promotion mix. Artotel Surabaya is one hotel that does many promotion mix activities, like advertising, publicity, direct marketing, and sales promotion. Based on good occupancy rate, the writers want to know whether the promotion mix has impacted on consumer purchase decisions in Artotel Surabaya. The results obtained are advertising, direct marketing, and sales promotion have impact to purchasing decisions of consumers, while publicity does not.